Enhancement Talking Students Ability Through Time Tokens Arends Technique in Social Sciences Learning. - Mardiah, Siti (Universitas Pendidikan Indonesia, 2017)
The research supported by the low ability to speak students For socialscience learning in class VII-E at SMP Negeri 26 bandung. This can beseen from livelines speak students Who only dominated by somestudents. While other students just stand still and not contributing within toconvey the ideas in front of the class. Seeing these problem, theresearcher choose Time Token Arends technique as a solution to increasetalking students ability. The purpose of this reseach is to describe aboutthe planning, implementation, improvement and reflection of theapplication of Time Token Arends technique to increase talking studentsability. The type of research that used is the class action Research (PTK)model Kemmis and Mc. Taggart which consists of four stages. The resultof this research. First, planning is done by determining the SK and KD,making the RPP and research instrument. Second, the implementation ofthe class action is performed according to the plan has been compiledpreviously so that to obtain the result with the quot;goodquot; category. Third, theconstraints during the execution of the research is to compile the materialsourced from the experience of the students so that they can increasecourage talking students. These constraint can be improved by discussingregarding the design of the materials with colleagues and partners. Fourth,the result of this research shows that there is an increased ability to talk onevery cycle. Cycle one students talking ability reaches the quot;enoughquot;category, the second cycle of students speaking ability reaches the quot;goodquot;category, third adn fourth cycles reach the quot;goodquot; category. So based onthis, then time token arends technique can increase students talkingability.